2023
DOI: 10.3390/w15132435
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Velocity and Reynolds Stress Distributions in a Straight Rectangular Channel with Submerged and Emergent Vegetation

Mohammad Reza Tabesh Mofrad,
Hossein Afzalimehr,
Parsa Parvizi
et al.

Abstract: Vegetation in rivers and streams plays an important role in preventing erosion and improving bank stability. Comparison between emergent vegetation (bank vegetation) and submerged vegetation, in terms of velocity and Reynolds stress distributions, for the same aspect ratio and flow discharge, has received limited attention in the literature. This study investigates the velocity and Reynolds stress, as well as the log law for submerged and emergent vegetation in a laboratory flume and compares the results for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The results showed that the vegetation pushed the flow toward the opposite bank and caused localized bank erosion. Lin et al [42] numerically and experimentally deduced the effect of emerged bank weeds on the velocity profiles. They concluded that the emerged bank weeds reduced the velocity near the bank and that the level of velocity reduction was proportional to the weed density due to the high drag of the weeds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the vegetation pushed the flow toward the opposite bank and caused localized bank erosion. Lin et al [42] numerically and experimentally deduced the effect of emerged bank weeds on the velocity profiles. They concluded that the emerged bank weeds reduced the velocity near the bank and that the level of velocity reduction was proportional to the weed density due to the high drag of the weeds.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the emerged bank weeds reduced the velocity near the bank and that the level of velocity reduction was proportional to the weed density due to the high drag of the weeds. Mofrad et al [42] presented an experimental comparison between the vegetation on the channel bed and the channel banks and their effects on the velocity distribution. The study proved that, in the case of the submerged vegetation (i.e., the bed vegetation), the location of maximum velocity was observed near the water surface.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of vegetation in rivers affects various aspects of the environment and aquatic systems, such as banks stability, sediment transport, water quality, and aquatic habitats. To address issues regarding river restoration and water conservation projects, the impacts of vegetation in rivers have attracted a lot of attention from researchers [17,18]. Tang et al [19] claimed that due to generation of secondary currents resulted from vegetation in the channel bed, the velocity for the incipient motion of bed material declined.…”
Section: Introductionmentioning
confidence: 99%